Analysis of Environmental Impact and Municipal Waste Management Strategy: A Case of the Piyungan Landfill, Yogyakarta, Indonesia - Ahmad Fakhurozi; Tatbita Titin Suhariyanto; Muhammad Faishal (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2021)
The ever-increasing volume of municipal waste in Yogyakarta brings overload capacity problems to the Piyungan Landfill. This circumstance results in environmental pollution which harms the local residents. Therefore, this study was conducted to determine the impact of pollution in the Piyungan Landfill from an economic, environmental, and social perspective. Furthermore, this study aims to formulate a waste management strategy in the landfill using the fishbone analysis to find out the root causes of existing problems, the stakeholder analysis method to determine the role of each stakeholder involved, and the SWOT analysis method to determine potential strategies for waste management. From those analysis methods, it is concluded that there are six root causes in the landfill, namely the waste management process, the amount of waste, landfill facilities, the technology used, the implementation process, and government policies. This study recommends several waste management improvements from the combination of strengths and opportunities factors (SO Strategy). The combination of these strategies includes: (1) establishing cooperation policies with foreign parties. (S1, O1); (2) optimizing budget and waste management technology. (S2, O2); (3) providing transportation facilities and technology to optimize the recycled waste business. (S3, O2, O3); and (4) maximizing resources to optimize the recycled waste business. (S4, O3). These strategies are expected to be able to increase the capacity and capability of the Piyungan Landfill in managing waste and overcoming environmental pollution.